PENDEKATAN SUPPLY-DEMAND UNTUK IDENTIFIKASI INDEKS KEKRITISAN AIR DI PULAU JAWA, INDONESIA - Santikayasa, I Putu; Okhy Wiranta, Dimas (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2022)
Water supply and demand are the most discussed issue in the world including in Indonesia. Java with the largest population and center for industrial and agricultural activities in Indonesia faces problems in water availability and water demand. This condition illustrates the potential of Java to experience water scarcity. This study analyzes water status in Java using the water balance approach and Water Scarcity Index. The analysis was carried out to evaluate changes in the annual water balance during a period of the 10-year average (1981-1990, 1991-2000, and 2001-2010). The rainfall data from CHIRPS and air temperature from CRU were used to calculate water availability. Water demand is calculated for the domestic, industrial, agricultural, and environmental sectors based on Indonesia water use standards. The results indicate that the average water availability in Java varies in each period. The highest water availability occurred in 1981-1990 (160 billion m3/year), while the lowest was in 1991-2000 (149 billion m3/year. The water availability decreased from 1981 to 2010, on a per capita basis. The water scarcity index also changes every period. The area experiencing a water deficit as described by their water scarcity index as a very critical class. Moreover, DKI Jakarta and East Java Provinces are in very critical condition with more than 50% area. Based on the study results, evaluation of water balance and water scarcity index can be used to describe the water status in a certain area as the reference for decision-makers in determining programs in water resources management.Keyword: Water status, water balance, water resources management, water scarcity, spatial analysis